Pressurized Microcystis can help to remove nitrate from eutrophic water. (January 2018) - Huang, Yingying; Chen, Xuechu; Li, Panpan; Chen, Guiqin; Peng, Lin; Pan, Liping
Graphical abstract: Highlights: Microcystis can be converted to a carbon source for N removal. Treated by pressurization at 0.4 MPa, Microcystis quickly sank to the bottom. Pressurization did not significantly affect the viability of Microcystis . Living Microcystis secreted DOC and enhanced N removal at the S/W interface. Abstract: The aim of this study was to investigate the feasibility of using harmful cyanobacterium Microcystis to help remove nitrate from eutrophic water. The results showed that after treatment by pressurization at 0.4 MPa, Microcystis quickly sank to the bottom. Pressurization did not significantly affect the viability of Microcystis and this cyanobacterium maintained high viability over three days under dark/anoxic conditions. Meanwhile, the amount of dissolved organic carbon (DOC) secreted from living Microcystis cells reached 2.48 mg C mg −1 Chl a, and a significant enhancement of pressurized Microcystis on nitrate removal at the sediment-water interface was observed, with a 2.85-fold increase in the specific NOX − -N removal rate. The results of this study support the novel idea that harmful Microcystis could be converted to a carbon source for removing nitrate from eutrophic water by a simple pressurization measure.